2017
DOI: 10.1080/13102818.2017.1358668
|View full text |Cite|
|
Sign up to set email alerts
|

The protective effect of melatonin and Ganoderma lucidum against the negative effects of extremely low frequency electric and magnetic fields on pulp structure in rat teeth

Abstract: Background/aim: The aim of this study was to determine whether Extremely low frequency electric and magnetic field (ELF-EMF) had any harmful effects on dental pulp tissue and examine histologically whether melatonin (MLT) and Ganoderma lucidum (GL) play a protective role against these harmful effects. Material and method: A total of 56 adult, male Wistar Albino rats were used in the study. The rats were separated into 8 equal groups and were exposed to ELF-EMF, generated by high voltage source, for 8 hours/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Tissues in the dental and jaws are also influenced by EMF. Periodontal tissues and the jawbone can also be affected (13). The obtained data is not enough to explain the interaction mechanisms between ELF-MF and oral tissues.…”
Section: Introductionmentioning
confidence: 80%
“…Tissues in the dental and jaws are also influenced by EMF. Periodontal tissues and the jawbone can also be affected (13). The obtained data is not enough to explain the interaction mechanisms between ELF-MF and oral tissues.…”
Section: Introductionmentioning
confidence: 80%
“…Melatonin, secreted from the pineal gland, has so far proved to be a good antioxidant. At the same time, many studies have reported that melatonin is protective against oxidative stress [14,18,19,20]. Researchers investigated the effect of melatonin on lipid peroxidation during radiotherapy in female rats.…”
Section: Discussionmentioning
confidence: 99%
“…A long-term electromagnetic field study found that testicular tissue showed no histological or morphological effects 24 . ELF-EMFs can induce histological changes in the dental pulp of rats, and the use of MLT and GI may have a protective effect against these changes 25 . In a study of mouse testes, observed degeneration and spermatogenesis in germ cells, a decrease in sertoli cells, necrosis in the epithelial germinal cells of seminiferous tubules, and atropia in seminiferous tubules 26 .…”
Section: Discussionmentioning
confidence: 99%